Shoot organogenesis and somatic embryogenesis from leaf and root explants of Scaevola sericea - Hanzhi Liang (Nature Portfolio, 2020)
Abstract An efficient regeneration system via shoot organogenesis and somatic embryogenesis from in vitro leaf and root explants was established for Scaevola sericea for the first time. The highest axillary shoot proliferation coefficient (4.8) was obtained on Murashige and Skoog (MS) medium supplemented with 1.0 mg/L 6-benzyladenine (BA) and 0.1 mg/L α-naphthaleneacetic acid (NAA) every 45 days. Young in vitro leaves and roots, which were used as explants, were cultured onto medium supplemented with different plant growth regulators. Our results showed that only cytokinins BA and thidiazuron (TDZ), could induce adventitious shoots and somatic embryos from leaf and root explants. The optimal medium to achieve this was MS medium supplemented with 2.5 mg/L BA and which induced most adventitious shoots (2.7) and somatic embryos (17.3) from leaf explants within 30 days. From root explants, 1.1 adventitious shoots and 7.6 somatic embryos could be induced on MS medium supplemented with 2.5 mg/L TDZ. Histological observation showed that both somatic embryos and adventitious shoots were originated from homogeneous parenchyma and the development of somatic embryos was visible. Maximum rooting percentage (99.0%) was achieved on half-strength MS medium supplemented with 2.5 mg/L NAA. Well-rooted plantlets, which were transplanted into a substrate of pure river sand, displayed a high survival percentage of 91.7% after transplanting for 45 days while the best substrate for plantlet growth was river sand: coral sand (1:1).